Comparison between the efficacy of neostigmine versus sugammadex reversal of rocuronium induced neuromuscular blockade in paediatric patients - Penny Tevaraj, Jasmine Mani (2016)
A reversal agent is commonly given to improve neuromuscular function after intra-operative administration of non-depolarizing neuromuscular blocking agents. The administration of conventional reversal agent neostigmine is associated with many undesirable side effects. For almost a decade, a new novel drug sugammadex has been used to specifically antagonize the effect of aminosteroidal neuromuscular blocking agents.The aim of this study is to compare the recovery time, haemodynamic stability and complications between these 2 reversal agents in antagonizing the effects of rocuronium in the paediatric population. This was a prospective, double-blinded, randomized controlled trial involving 80 paediatric patients aged between 2-12 years old scheduled for surgery under general anaesthesia requiring rocuronium induced neuromuscular blockade.They were randomized equally into two groups, 40 patients each group for reversal with neostigmine or reversal with sugammadex. All patients were induced with sevoflurane, intravenous access obtained, then 2mcg/kg of fentanyl was administered. Neuromuscular function monitoring (acceleromyography) of the adductor pollicis muscle was done using train-of-four (TOF) method. TOF-Watch Sx was placed along the ulnar groove of the hand and calibrated. After a baseline TOF reading was taken, and 0.6mg/kg of rocuronium was given. Patients were intubated once TOF count was less than 1. TOF was monitored and maintained at count of 2-3 throughout the surgery by administering 0.2mg/kg of rocuronium once TOF count was more than 3. The haemodynamic parameters pre-reversal and post-reversal was documented. The neuromuscular recovery time, from reversal administration at TOF count 2 or 3 to TOF ratio 0.9 was documented. Any complications observed postextubation were documented. The neuromuscular recovery time from TOF count 2 or 3 to TOF ratio 0.9 post-reversal was significantly higher in the neostigmine group, with a mean of 501.58 seconds as compared to only 84.45 seconds in the sugammadex group.The mean difference was 417.13 seconds. This difference was statistically significant evidenced by p<0.05. There were also significant changes in the means of systolic blood pressure, diastolic blood pressure and mean arterial pressure pre-reversal and post-reversal in both groups. However the mean differences were much lower in the sugammadex group, ranging from -2.38 to -2.93 as compared to the neostigmine group, which were from -4.85 to -6.80. The mean heart rate pre-reversal and postreversal showed significant changes in the neostigmine group, but the changes were not significant in the sugammadex group. The incidence of complications postreversal was higher in the neostigmine group with 17.5% (7 patients) post-operative nausea vomiting and 2.5% (1 patient) sweating. There were no complications noted in the sugammadex group. Sugammadex has a significantly shorter recovery time (from TOF count of 2 or 3 to TOF ratio of more than 0.9) as compared to neostigmine. Sugammadex has a more stable haemodynamic profile as compared to neostigmine when used to reverse rocuronium induced neuromuscular blockade in paediatric patients. Sugammadex causes less complications or side effects when used in paediatric patients as a reversal for rocuronium induced neuromuscular bloackade.